2023
DOI: 10.1111/sode.12663
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different types of social norms on children's sharing behavior: The roles of parents, teachers, and peers

Abstract: As children develop, they are exposed to social norms that help them adapt to society. Here, the current study used an adapted dictator game to investigate whether exposure to a generous norm (sharing 80 yuan) or a selfish norm (sharing 20 yuan) would influence the sharing behavior of children. Participants were 1983 third‐ to fifth‐graders from five primary schools in mainland China (two in Beijing and three in Shandong). Norms were presented in the written format in which children were told the amount of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This agrees with the recommendations to evaluate the operationalization of the construct in a specific cultural, social, and professional framework [ 56 , 72 , 73 ], particularly one where prosociality becomes a relevant job skill [ 72 , 73 ] and—in the specific case of the context studied—authenticated by regulatory requirements [ 51 , 52 ]. Although possibly comparable in different degrees and forms of operationalization, the actions of helping [ 36 , 37 ], sharing [ 38 ], caring [ 39 , 40 , 41 ], and feeling empathy [ 32 , 43 , 44 , 45 , 46 , 47 , 48 ] constitute expressions of prosociality in various teaching scenarios, and it is displayed on multiple levels [ 1 ]. One is the micro-intrapersonal, which refers to dispositions and tendencies; another is the meso-intrapersonal, concerning behaviors directed to a person or small groups [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with the recommendations to evaluate the operationalization of the construct in a specific cultural, social, and professional framework [ 56 , 72 , 73 ], particularly one where prosociality becomes a relevant job skill [ 72 , 73 ] and—in the specific case of the context studied—authenticated by regulatory requirements [ 51 , 52 ]. Although possibly comparable in different degrees and forms of operationalization, the actions of helping [ 36 , 37 ], sharing [ 38 ], caring [ 39 , 40 , 41 ], and feeling empathy [ 32 , 43 , 44 , 45 , 46 , 47 , 48 ] constitute expressions of prosociality in various teaching scenarios, and it is displayed on multiple levels [ 1 ]. One is the micro-intrapersonal, which refers to dispositions and tendencies; another is the meso-intrapersonal, concerning behaviors directed to a person or small groups [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another type of aid is the action of sharing. Generous teachers can serve as role models and encourage children to take actions aimed at sharing and giving to others [ 38 ]. In addition, among the contributors to academic and social success are the caring actions practiced at school in the context of teacher–student relationships [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of Experiment 2, moral constraints and reputation constraints, that is, considering moral rules and reputation, will affect sharing behaviors in humanrobot teams. Previous studies have shown that social norms affect human sharing behaviors (Wei et al, 2023), with morality and reputation being two important foundation. Sharing behaviors that conform to social norms is crucial for establishing and maintaining social relationships (Strauß and Bondü, 2023).…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
“…The study also examined children's expectations for how a teacher, the primary conveyor of social norms and the most authoritative adult in children's daily lives (Benozio & Diesendruck, 2017; Wei et al., 2023), would allocate resources. As a common indicator in examining children's resource allocation (Elenbaas & Killen, 2016; Paulus et al., 2014; Rizzo et al., 2020), expectations can offer important insight into children's perceptions of the social norms surrounding resource allocations and show whether they are different from allocation behaviors.…”
Section: Introductionmentioning
confidence: 99%